A simple route to complex materials: the synthesis of alkaline earth – transition metal sulfides. Issue 72 (25th August 2017) - Al-Shakban, Mundher; Matthews, Peter D.; O'Brien, Paul
Abstract : A simple, low-temperature synthesis of a family of alkaline earth metal chalcogenide thin films is reported. Abstract : A simple, low-temperature synthesis of a family of alkaline earth metal chalcogenide thin films is reported. These materials have previously only been produced from demanding, high temperature, high pressure reactions. The decomposition of calcium, barium and copper xanthates leads to the clean formation of CaS, BaS, CaCu2 S2, β-BaCu2 S2 and β-BaCu4 S3 .